2017
DOI: 10.1111/cbdd.12983
|View full text |Cite
|
Sign up to set email alerts
|

Identification of natural inhibitors of Bcr‐Abl for the treatment of chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is a clonal myeloproliferative disorder of the hematopoietic stem cells, characterized at the molecular level by the bcr/abl gene rearrangement. Even though targeting the fusion gene product Bcr-Abl protein is a successful strategy, development of drug resistance and that of drug intolerance are currently the limitations for Bcr-Abl-targeted CML therapy. With an aim to develop natural Bcr-Abl inhibitors, we performed virtual screening (VS) of ZINC natural compound database by doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Chronic myelogenous leukemia (CML) is a major hematopoietic disorder marked by the presence of the Philadelphia chromosome (Ph), which is generated when chromosomes 9 and 22 break and exchange their parts [1,2]. This alteration can result in the aberrant activation of Bcr-abl kinase [3,4], which in turn can regulate the aberrant tumorigenesis through stimulating the initiation of diverse signal transduction pathways, including a mitogen-activated protein kinase (MAPK), and a Janus kinase/signal transducer and activator of transcription (JAK/STAT), and the phosphatidylinositol 3 kinase (PI3K) signaling pathway, and the nuclear factor-κB (NF-κB) [5][6][7][8][9]. Imatinib mesylate is the primary tyrosine kinase that has been used to target Bcr-abl and has been clinically approved for the management of CML [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic myelogenous leukemia (CML) is a major hematopoietic disorder marked by the presence of the Philadelphia chromosome (Ph), which is generated when chromosomes 9 and 22 break and exchange their parts [1,2]. This alteration can result in the aberrant activation of Bcr-abl kinase [3,4], which in turn can regulate the aberrant tumorigenesis through stimulating the initiation of diverse signal transduction pathways, including a mitogen-activated protein kinase (MAPK), and a Janus kinase/signal transducer and activator of transcription (JAK/STAT), and the phosphatidylinositol 3 kinase (PI3K) signaling pathway, and the nuclear factor-κB (NF-κB) [5][6][7][8][9]. Imatinib mesylate is the primary tyrosine kinase that has been used to target Bcr-abl and has been clinically approved for the management of CML [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…1). Both the compounds have indicated the formation of an H bond with MET 318 with the hydroxyl group of the curcumin and derivative scaffold which has been previously observed as a key interaction (Parcha et al 2017). The additional hydrogen-bond interaction formed by the curcuminsemicarbazide complex was ILE 313 which has been previously reported to be favorable interaction for the complex (Zhou et al 2016).…”
Section: Discussionmentioning
confidence: 64%
“…The interaction of TQ with the active site of BCR-ABL revealedless affinity and higher free binding energy than imatinib.The results agree with previous findings that revealed that two ZINC natural compounds, ZINC08764498 and ZINC12891610, have potential binding affinities toward BCR-ABL oncoprotein. 31 The docked conformation of PI3K, Akt, and mTOR proteins clearly showed numerous potential interactions with TQ's active conformation (Figures 3, 4, and 5). The chemical interaction between TQ and PI3K showed a pi sigma bond with ILE933, a Pi sulfur bond to CYS883, a pi lone pair to THR886, and five alkyl bonds to VAL930, ARG894, HIS909, ILE899, and PHE938 with a free binding energy of -7.02 Kcal/mol (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%